Educometrics: from theory to application - Silva, Thomaz Edson Veloso da (2017)
Nowadays, in the educational context, emphasis has been placed on the collection and analysis of data by scientists from several areas of knowledge, such as: psychology and economics. These professionals analyze data and their results can be used, for example, to aid in the decision making of a public policy. However, educational measures have become very popular and can encompass all the multidimensionality contained in the educational process, from teaching and learning to social interaction in the classroom. Understanding of data analysis in a classroom needs to be done by teachers and pedagogues who know exactly the empirical significance of the variability of a particular measured variable. In this sense, this thesis conceptualizes, discusses, defines and applies Educometrics, which is recognized as an area of knowledge that makes use of multivariate statistical models to analyze data related to educational contexts. After establishing the concept of Educometrics, we apply some mathematical models in the learning context of teaching in distance learning. A sample of 791 students answered the updated QEOn questionnaire for three courses and the factorial structure of the questionnaire was valid from the application of factorial analysis. The principal component analysis and the Parafac2, bilinear and multilinear models, respectively, were applied and able to identify intrinsic behaviors in relation to the 34 statements contained in the QEOn questionnaire. As a conclusion, the application of models that allow pedagogical intervention in the classroom as it is the key of the support provided by the educometrics developed throughout this thesis.